THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF NUMBERED HEAD TOGETHER (NHT) TYPE WITH GROUP INVESTIGATION (GI) TOWARD THE STUDENTS OF SMP MUHAMMADIYAH PLERET - Paradita Widyaswari; Harina Fitriyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The use of a group learning model that has not varied and the students’ role which less active in the learning process can influence the students learning outcome so that it is important to choose an innovative learning model where the students can involve in the learning process actively. The problem underlying the research by using a cooperative learning model which its types namely Number Head Together (NHT) and Group Investigation (GI). This research is conduct to know the effectiveness of cooperative learning model types NHT and GI toward the students of SMP Muhammadiyah Pleret grade VII in the academic year of 2015/2016. The population of this research was the student’s grade VII of SMP Muhammadiyah Pleret in the academic year of 2015/2016. The sample collecting technique used in this research was random sampling and grade VII A was chosen as the class which is given cooperative learning with the NHT type and grade VII C as the class that using cooperative learning which is the type namely GI. The data collecting technique used test technique. The research instrument in this research was the mathematic result test which is the objective questions as the test questions. The instrument test includes validity, different power, and reliability. The data analyzing technique used the prerequisite test analysis which consists of a normality test and homogeneity test. The hypothesis test used a one-tailed t-test and a two-tailed t-test. Based on the calculation of the two-tailed t-test with  significance level  α = 5% and 55 degrees of freedom obtained and  and then  it means there are differences in the mathematic result study between students who use cooperative learning model types NHT with the students who use GI. One-tailed t-test with significance level α = 5% and 55 degrees of freedom obtained  = 2,125403947 and  so   in conclusion, the student’s mathematic learning outcome who uses cooperative learning model NHT is more effective than GI.